Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.34067/kid.0007962021
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposures and Kidney Disease

Abstract: Accumulating evidence underscores the large role played by the environment in the health of communities and individuals. We review the currently known contribution of environmental exposures and pollutants on kidney disease and its associated morbidity. We review air pollutants, such as particulate matter; water pollutants such as trace elements, per- and polyfluorooakyl substances, and pesticides; and extreme weather events and natural disasters. We also discuss gaps in the evidence which at present relies he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Another study found that glyphosate use and the intensity of exposure were related to serum creatinine, but not to eGFR [ 50 ]. Some pesticides used by farmers in this study, such as alachlor, atrazine, glyphosate, paraquat, and permethrin, have been linked to CKD [ 51 ]. According to our findings, long-term pesticide exposure may cause nephrotoxic changes and increase the risk of CKD in vegetable farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that glyphosate use and the intensity of exposure were related to serum creatinine, but not to eGFR [ 50 ]. Some pesticides used by farmers in this study, such as alachlor, atrazine, glyphosate, paraquat, and permethrin, have been linked to CKD [ 51 ]. According to our findings, long-term pesticide exposure may cause nephrotoxic changes and increase the risk of CKD in vegetable farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution contributes to over 4 million deaths annually [34 & ]. The association of air pollution, especially PM 2.5 , is with kidney dysfunction as reviewed elsewhere [33,47]. Literature on the impact of PM 2.5 on kidney development is scarce, however PM 2.5 and ozone exposure are associated with an up to 20% increased risk of LBW, a programming impact on fetal kidney development must be considered [34 & ].…”
Section: Air Pollutionmentioning
confidence: 99%
“…The consequences of wildfire smoke exposure extend beyond the respiratory system [ 6 ]. Particulate matter (PM) reflects the organic and inorganic particles in solid and liquid form suspended in the air [ 33 ]. PM is classified by particle size.…”
Section: Wildfiresmentioning
confidence: 99%
“…Renal failure development was also correlated with blood-Pb levels [56] a slower decline in renal function following lead chelation therapy [57]. Some publications claim that Cd and Pb may be responsible for the overall progression of renal disease [58]. The results showed that there is no significant increase in the tests compared to the control.…”
Section: Heavy Metals In Serum Blood Ckdmentioning
confidence: 99%